Recurrent congenital cytomegalovirus infection in a sequential pregnancy with severe sequelae, and a possible association with prophylactic valacyclovir treatment: a case report. (December 2022) - Brosh-Nissimov, Tal; Benshalom-Tirosh, Neta; Bucris, Efrat; Morad, Hagar; Zuckerman, Neta S.; Tepperberg Oikawa, Michal
Highlights: Recurrent vertical cytomegalovirus transmission in sequential pregnancies with sequellae. Valacyclovir treatment during primary infection might delay adaptive immunity. A longer delay after treatment of primary infection is suggested before conception. Abstract: Recurrent congenital cytomegalovirus infections in consecutive pregnancies are rarely reported. Due to the risk of fetal infection from preconception maternal infection, a 6-month interval after primary maternal infection is generally advised before a new conception. Recently, high-dose valacyclovir treatment was shown to prevent fetal infection in first trimester primary infections. We present a case of first trimester primary infection treated with high-dose valacyclovir but resulting in polymerase chain reaction–confirmed fetal infection. Cytomegalovirus-specific immunoglobulin G titers remained very low during treatment and rose only after cessation of antiviral treatment. Six months after primary seroconversion, in a sequential pregnancy, recurrent fetal infection was diagnosed and resulted in severe fetal sequella. Whole genome sequencing of both amniotic fluid isolates proved them to be identical. Both pregnancies were terminated. We hypothesize that valacyclovir treatment, although unsuccessful in preventing fetal infection, had delayed the adaptive maternal immune response and might have contributed to fetal infection during the sequential pregnancy. We suggest that a longer delay might be warranted after valacyclovir treatment and before a new conception.